The Reason, We Should be “Critical”: Critical Reflections on Positivist International Relations Theories, Focusing and Critical Theory - Lee, Yoochul (Journal of Posthumanism, 2025)
The purpose of this study is to critique the positivist international political theories distinguished as mainstream international political theories and to explore the potential of critical theory as an alternative international political theory. To this end, this paper examines the positivism of mainstream international politics and its problems and critically analyzes the significance of the ontological shift in international political theory. Furthermore, it discusses the direction of international political theory through the relevance of critical theory as a value-laden theory.International politics, as the term suggests, encompasses inter-state relations, signifying the manifestation of sociality. The absence of contemplation on essence leads to the neglect of inherent identity and history. The sociality and capitalist order that constitute states create the possibility of a grand theory. In this respect, this study focuses on critical theory.This study is significant in that it examines the potential of critical theory in international political theory, moving away from mainstream international political theories. The attempt to find potential in critical theory, which has been neglected in the field of international political studies, holds significant meaning. Additionally, this study holds academic relevance as it is a meta-theoretical approach rather than a study of current issues.